2015
DOI: 10.1080/15476286.2015.1048957
|View full text |Cite
|
Sign up to set email alerts
|

MiR-2 family targetsawdandfngto regulate wing morphogenesis inBombyx mori

Abstract: (2015) MiR-2 family targets awd and fng to regulate wing morphogenesis in Bombyxmori, RNA Biology, 12:7, 742-748, DOI: 10.1080/15476286.2015 Keywords: CRISPR/Cas9, Gal4/UAS, miR-2 cluster, transgene, wing disc MicroRNAs (miRNAs) are post-transcriptional regulators that target specific mRNAs for repression and thus play key roles in many biological processes, including insect wing morphogenesis. miR-2 is an invertebrate-specific miRNA family that has been predicted in the fruit fly, Drosophila melanogaster, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…PiRNA sequences were found by referring to Kawaoka et al . [ 11 ], and the relative expression was measured using the stem-loop method [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…PiRNA sequences were found by referring to Kawaoka et al . [ 11 ], and the relative expression was measured using the stem-loop method [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, Juvenile hormone esterase ( JHE ) was deleted in silkworms to extend the larval growth period, resulting in larger larvae and cocoons, which results in more silk production (Zhang et al ., ). In another example, knockout of abnormal wing disc ( awd ) and fringe ( fng ) resulted in deformed wings; these gene products are potential targets for control of lepidopteran pests (Ling et al ., ). Our study of the silkworm, which is a model lepidopteran insect, suggests that inhibition of the Hippo pathway should be investigated as a means for control of lepidopteran pests.…”
Section: Discussionmentioning
confidence: 97%
“…It has also been shown to participate in the regulation of apoptosis of neuroblasts during the normal development of the nervous system in Drosophila 70 . Recent evidence shows that miR-2 regulates functions essential for the normal wing morphogenesis of B. mori via targeting of awd and fng 71 . Alexandra’s group revealed that miRs-2/13, including miR-2a, miR-2b, miR-13a, and miR-13b, play an important regulatory part in the embryonic development of Drosophila by targeting nine genes, including Sos and Myd88 72 .…”
Section: Discussionmentioning
confidence: 99%